Vesicoureteral Reflux, a Scarred kidney, and Minimal Proteinuria: An Unusual Cause of Adult Secondary Hypertension - Shaifali Sandal; Apurv Khanna (Case Reports in Medicine)
Hypertension affects about 65 million individuals in the United States. In adult patients, primary aldosteronism and renovascular causes are described as most prevalent. Vesicoureteral reflux as a cause of hypertension, while commonly described in pediatric populations, is less prevalent in the adult population especially in the absence of proteinuria. We present the case of a 31-year-old female presenting with early onset hypertension. Workup for renovascular hypertension was unrevealing. She was found to have right-sided vesicoureteral reflux with a unilateral scarred kidney. Patient underwent a nephrectomy with marked improvement in blood pressure control.